Sub-Telomeric core X and Y' Elements in S.cerevisiae Suppress Extreme Variations in Gene Silencing - Power, Patricia (Public Library of Science, 2011)
Telomere Position Effect (TPE) is governed by strong repression signals emitted by telomeres via the Sir2/3/4 Histone Deacetylase complex. These signals are then relayed by weak proto-silencers residing in the subtelomeric core X and Y' elements. Subtelomeres also contain Sub-Telomeric Anti-silencing Regions (STARs). In this study we have prepared telomeres built of different combinations of core X, Y' and STARs and have analyzed them in strains lacking Histone-Acetyltransferase genes as well as in cdc6-1 and Δrif1 strains. We show that core X and Y' dramatically reduce both positive and negative variations in TPE, that are caused by these mutations. We also show that the deletion of Histone-Acetyltransferase genes reduce the silencing activity of an ACS proto-silencer, but also reduce the anti-silencing activity of a STAR. We postulate that core X and Y' act as epigenetic “cushioning” cis-elements.